The political economy of agroecological transitions: Key analytical dimensions - McKay, Ben M.; Nehring, Ryan; Catacora-Vargas, Georgina (Informa UK Limited, 2025)
There is a growing global interest in agroecology, yet agroecological transitions remain fraught with challenges. These include the need to reconfigure the productive and reproductive agrarian relations of unsustainable food systems and to rethink how we work with ecosystems. Using a political economy approach, we propose five key interrelated dimensions for analyzing agroecological transitions: (i) social metabolism; (ii) labor dynamics; (iii) markets and resources; (iv) social organization; and (iv) policies and politics. While these dimensions are often analyzed separately and to varying degrees, we argue that together they contribute to a comprehensive analysis of the political economy of agroecological transitions.